2013
DOI: 10.1037/a0032008
|View full text |Cite
|
Sign up to set email alerts
|

The co-occurrence of pain and depression in adults with multiple sclerosis.

Abstract: Purpose/Objective To define the rates of pain, depression, and their co-occurrence in persons with multiple sclerosis (MS). Research Method/Design Participants were 161 persons with MS who previously participated in research and indicated a willingness to be contacted for future studies. Data were collected via postal survey and included the Patient Health Questionnaire—9 for depressive symptoms and a numerical rating scale (0–10) for pain. Descriptive statistics, chi-square analyses, and odds ratios were ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 21 publications
2
25
0
Order By: Relevance
“…Significant correlations between average symptom levels are consistent with previous cross-sectional research concluding that pain, fatigue, and depressive and cognitive symptoms often cluster together in ms 4,23,26,27,29,30,4850 . Taken together, these findings underscore the importance of considering both between-person and within-person processes; for example, although the extant data support the hypothesis that people who report higher depressed mood also report higher pain, these data suggest that when a person feels particularly depressed, they are not more likely to experience a subsequent increase in pain on a typical day.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Significant correlations between average symptom levels are consistent with previous cross-sectional research concluding that pain, fatigue, and depressive and cognitive symptoms often cluster together in ms 4,23,26,27,29,30,4850 . Taken together, these findings underscore the importance of considering both between-person and within-person processes; for example, although the extant data support the hypothesis that people who report higher depressed mood also report higher pain, these data suggest that when a person feels particularly depressed, they are not more likely to experience a subsequent increase in pain on a typical day.…”
Section: Discussionsupporting
confidence: 89%
“…Research examining associations between commonly comorbid symptoms in MS is increasing. For instance, studies that have considered multiple MS symptoms have consistently identified pain, fatigue, depressed mood 23, 2630 , and cognitive problems 24, 31 as symptoms that cluster together. Although these studies have advanced our understanding of how symptoms correlate in MS, a number of questions about the nature of these symptoms remain.…”
mentioning
confidence: 99%
“…One medium quality study [64] showed that headache severity and depression (BDI-II) were unrelated. In terms of odds ratios, one medium [65] and one good quality study [66] showed that MS participants meeting the depression criteria were 1.196-2.070 times more likely to meet the pain criteria (greater severity) relative to non-depressed MS participants.…”
Section: Depressionmentioning
confidence: 97%
“…This may be a result of the occurrence of secondary psychopathological symptoms during the illness, of which the most common are depressive symptoms in about 11%-34% (Alschuler, Ehde, & Jensen, 2013) of multiple sclerosis patients and fatigue in about 70%. The fatigue is considered one of the disease's three main symptoms (Losy, 2005).…”
Section: Psychological Consequences Of Multiple Sclerosismentioning
confidence: 99%